SAR oil spill imaging, interpretation and information retrieval techniques - Brekke, Camilla; Jones, Cathleen Elaine (The Institution of Engineering and Technology (IET), 2020)
This chapter addresses the physical mechanisms behind SAR imaging of oil spills in the open ocean and proceeds with a discussion on the emerging SAR information retrieval techniques for detecting and characterizing these slicks. Section 9.1 covers oil spill information items possibly derived from SAR and limitations of existing methods. Challenges and trade-offs faced by operational service providers in retrieving these items are discussed in Section 9.2. Section 9.3 is about SAR image interpretation: the main contrast drivers for oil spills are explained and surface scattering models aiding interpretation are reviewed. In Section 9.4, the main techniques for oil spill detection and characterization are illustrated and current research questions are discussed. Concluding remarks and notes on further readings are given in Section 9.5.